2020
DOI: 10.33258/birle.v3i2.899
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Novice Writers with Creative Writing Workshop in Poetry Writing Classroom (Indonesian EFL Context)

Abstract: The increasing usage of creative writing strategy in a poetry writing classroom can nevertheless answer the question which has been empirically explored throughout the decade; Can second language learner write a poem in their non-native tongue? This study aimed to answer whether the creative writing strategy can facilitate novice writers who are the third year of English Department undergraduate students to be able to write an English poem. The strategies cover written prompts dealing with their personal exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Creativity is one of the important skills in the 21st-century of learning. it is often related to the term "out of the box" meaning that the students can go beyond the original thing (Sari et al, 2020;Zhao, 2014) (Zhao, 2014). Based on the result of the interview, it is found that students' creativity existed in writing Haiku.…”
Section: Promoting Students' Creativity In Writingmentioning
confidence: 99%
“…Creativity is one of the important skills in the 21st-century of learning. it is often related to the term "out of the box" meaning that the students can go beyond the original thing (Sari et al, 2020;Zhao, 2014) (Zhao, 2014). Based on the result of the interview, it is found that students' creativity existed in writing Haiku.…”
Section: Promoting Students' Creativity In Writingmentioning
confidence: 99%
“…Puisi adalah salah satu jenis karya sastra yang telah terbukti keampuhannya dalam mendorong pembelajaran bahasa dan mengembangkan keterampilan menulis (Hanauer, 2012;Widodo, et. al., 2016;Iida & Chamcharatsri, 2020;Sari, et. al., 2020;Fithriani, 2021).…”
Section: Pendahuluanunclassified
“…Writing skills are very important to learn because writing skills are very important in supporting student success (Kristyanawati, 2019). Still, the thought of writing in a second language hinders their creativity (Sari, 2020). The practice is frequently beneficial as preparation for other activities such as sharing ideas, feelings, and all of one's thoughts with others (Suastra & Menggo, 2020).…”
Section: Introductionmentioning
confidence: 99%